2016
DOI: 10.1016/j.jhazmat.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of electroremediation in real contaminated sediments using a big cell, periodic voltage and innovative surfactants

Abstract: The present work focused on evaluating the electrokinetic (EK) treatment of real contaminated sediments with toxic metals and polycyclic aromatic hydrocarbons (PAHs), using a big laboratory EK cell, periodic voltage and recently tested non-ionic surfactants. The results indicated that the "day on-night off" application mode of voltage, in conjunction with the selected solubilising agents, favoured the overall EK process. Arsenic, nickel and chromium exhibited the highest removal percentages, obtaining 83%, 67%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 51 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Although EK approaches have been applied for decades to enhance contaminant migration, recent work shows the technology offers new promise if applied to deliver remediation reagents into low‐permeability zones and increase overall reagent distribution uniformity in geologically heterogeneous settings. A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al ), lactate and bacteria (Mao et al ), and surfactants (e.g., Hahladakis et al ). More specifically, in laboratory experiments, Mao et al () were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE.…”
Section: Electrokinetic‐enhanced Reagent Deliverymentioning
confidence: 99%
“…Although EK approaches have been applied for decades to enhance contaminant migration, recent work shows the technology offers new promise if applied to deliver remediation reagents into low‐permeability zones and increase overall reagent distribution uniformity in geologically heterogeneous settings. A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al ), lactate and bacteria (Mao et al ), and surfactants (e.g., Hahladakis et al ). More specifically, in laboratory experiments, Mao et al () were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE.…”
Section: Electrokinetic‐enhanced Reagent Deliverymentioning
confidence: 99%
“…EDTA is a complexing agent that can increase solubilization of hydrophobic contaminants but due to high alkalinity and toxicity, EDTA provides losses to microbial activities and communities in soil (Dong et al, 2013;Hahladakis et al, 2016;Kim et al, 2010). β-cyclodextrin contained in the starch is known to be used to improve the electrokinetic bioremediation process of contaminated soil.…”
Section: Electrolyte Characteristicmentioning
confidence: 99%
“…Specifically, the 4-6 ring PAHs are toxic and carcinogenic to humans, which are recalcitrant to biodegradation by indigenous microorganism (Moon et al, 2006;Mousset et al, 2014;Biache et al, 2015). Consequently, there is significant emphases placed on remediation technologies that can effectively degrade PAHs in soils (Hahladakis et al, 2016;Bezza and Chirwa, 2016;Ranc et al, 2016).…”
Section: Introductionmentioning
confidence: 99%